Protein сontent and cheesemaking quality of different breeds of milk cows - Шаповалов, С. О.; Аль-Бази Мезхер, Камиль (Scientific Progress & Innovations, 2012)
The article describes the materials of study of protein and cheese making quality of milk from cows of three breeds: Simmental, Red and White and Black and White. The tasks of the research was to determine the fractional composition (mass fraction of casein and its fractions, albumin and globulin) and amino-acid composition of proteins (the ratio of essential and nonessential amino acids, their scores, the definition of limiting amino acids in the protein of milk of each breed), the rate of coagulation and quality of milk clot formed under the action of rennet.